Servant of Mut : studies in honor of Richard A. Fazzini - D'Auria, Sue.; Fazzini, Richard A. (Probleme der Ägyptologie ;, 2008)
Richard A. Fazzini has inspired and mentored many scholars of Egyptology through his tireless efforts as curator and then chairman of the Brooklyn Museum's Deptartment of Egyptian, Classical and Ancient Middle Eastern Art (ECAMEA); field archaeologist of the Pricinct of Mut at Karnak; scholar; and teacher, The 35 contributions to this volume in his honor represent the variety of Professor Fazzini's own research interests namely in ancient Egyptian art, religious iconography, and archaeology, particularly of the New Kingdom, Third Intermediate Period, and Late Period. Reflections on Professor Fazzini's scholarship and teaching are accompanied by an extensive bibliography of his works.